2008
DOI: 10.3171/spi/2008/9/8/129
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for subsequent vertebral fracture after percutaneous vertebroplasty

Abstract: Object The purpose of this study was to evaluate the predictive factors for subsequent vertebral fracture occurring after percutaneous vertebroplasty (PVP) at the neighboring levels (adjacent vs nonadjacent levels). Methods The medical records of 508 consecutive patients treated with PVP between January 2000 and December 2002 were retrospectively reviewed. A total of 45 patients with 49 painful vertebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 24 publications
8
80
1
1
Order By: Relevance
“…20 Moreover, many reports agree with the fact that fracture risk of adjacent segment vertebra increases after vertebroplasty. [21][22][23] It has been reported that vertebroplasty should be performed for fewer than three vertebral bodies. 24 Fracture instability due to biomechanical change is the main reason for pain in VBCF, 25 and thus nonunion and unstable vertebrae are the therapeutic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…20 Moreover, many reports agree with the fact that fracture risk of adjacent segment vertebra increases after vertebroplasty. [21][22][23] It has been reported that vertebroplasty should be performed for fewer than three vertebral bodies. 24 Fracture instability due to biomechanical change is the main reason for pain in VBCF, 25 and thus nonunion and unstable vertebrae are the therapeutic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Various reasons and risk factors for fractures that occur following VP have been discussed: increased stiffness in the vertebra treated [34,42], cement formation of a solid mass rather than interdigitation [43], changes in load transfer [44,45], an altered loading direction [46], cement leakage into the disc (pro: [12,14,21,[47][48][49], contra: [50]), use of too much cement [15,49], the degree of vertebral height restoration [12,15] and persistent local kyphosis [20], deflection of the endplate and the intervertebral disc into adjacent vertebra [34], fracture shape [51], pre-existing fracture [12,23], advanced patient age [23], ongoing osteoporosis [16,20,24], and low BMD [12,16,19,21,23], and a high number of VPs at baseline [16,26]. In addition, patients with high parathyroid hormone concentrations, low body mass index, no use of back brace, no anti-osteoporosis therapy, history of metabolic disease, and use of drugs which influence bone metabolism tend to have a greater risk of recurrent fractures [16,17,47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with high parathyroid hormone concentrations, low body mass index, no use of back brace, no anti-osteoporosis therapy, history of metabolic disease, and use of drugs which influence bone metabolism tend to have a greater risk of recurrent fractures [16,17,47]. Studies on refractures of augmented vertebrae focused on the influence of vertebral height restoration, distribution patterns of cement in the augmented vertebra and intravertebral clefts [52], pre-operative osteonecrosis [18,53], fracture shape, loading case and elastic modulus of fracture region and cement [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are controversies regarding the optimal volume and location of the injected cement. Adjacent fractures are related to strength differences associated with cement augmentation, and non-adjacent fractures are due to differences in segmental mobility 1) . Increased vertebral strength after vertebroplasty can cause a spontaneous vertebral compression fracture without any obvious traumatic event 6) .…”
Section: Introductionmentioning
confidence: 99%